Unlocking Global Opportunities for Creative Smes: The Case of CV. Aura Sufa’s Internationalization Journey - Suwarni, Evi; Lestari, Baroroh; Wahyu, Ellyn Eka; Kusumasasti, Ika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to identify the internationalization strategies adopted by UMKM CV. Aura Sufa, a small enterprise focused on food production, in entering global markets. A qualitative approach was employed, utilizing interviews and documentation to gather data over seven months, from March to October 2024. The study shows that internationalization of small-medium enterprises (SMEs) is achievable through strategic partnerships, product diversification, and governmental support, particularly through initiatives such as Export Center Surabaya. CV. Aura Sufa successfully penetrated the Taiwanese market by leveraging unique fruit-based products, which demonstrate the potential for local businesses to thrive globally. Key challenges faced include production capacity limitations and language barriers. The findings highlight the importance of continuous innovation and networking in sustaining international market presence. This research offers valuable insights for both practitioners and policymakers to enhance the competitiveness and sustainability of SMEs, helping to align strategies with future market trends and government policies.